Investment opportunities, free cash flow and market reaction to international joint ventures - Chen, Sheng-Syan; Ho, Kim Wai; Lee, Cheng-few; Yeo, Gillian H.H. (Journal of Banking & Finance, 2000)
This paper examines the role of investment opportunities and free cash flow in explaining the source of the wealth effect of international joint ventures. We document that firms with promising investment opportunities have significantly positive response to announcements of international joint venture investments, whereas firms with poor investment opportunities have unfavorable response to such announcements. In contrast, we find that free cash flow does not explain the cross-sectional differences in abnormal returns associated with the announcements of international joint ventures. Thus, our results show support for the investment opportunities hypothesis but no support for the free cash flow hypothesis. These findings hold even after controlling for other potential explanatory variables.